Human Rights Violations: An Impetus for Police Reforms in Kenya Between 1978 and 2002 - Mwangi, Susan (2020)
Since independence, police reforms have been influenced by the need to expand democratic space and to ensure protection of human rights. Previous studies have attempted to deconstruct the police reforms. However, the studies have not adequately examined the implications of police reforms on human rights in Kenya. This paper examines police reforms between in Kenya between 1978 and 2002 and their implications on human rights. The study was based on a descriptive survey design and targeted senior serving and retired police officers, government administrators, county government administrators and members of the human rights groups in Nairobi County. Purposive sampling technique was used to select 116 study participants. Data was collected through focus group discussion, interview schedule and document analysis and analyzed based on thematic content analysis. The study findings revealed that Moi’s presidency (between 1978 and 2002) was marked by minimal police reforms but heightened human rights violation including arrests without warrants, detention without trial and torture which resulted in injury and death. This implied that in the absence of substantive reforms, the police disregarded human rights. Hence, the period between 1978 and 2002 was marked by curtailed freedom of association, assembly, speech and expression.Keywords: Human Rights, Police Reforms, human rights discourse, Moi era, Kenya DOI: 10.7176/JLPG/103-06 Publication date: November 30th 202